Network Pharmacology and Computational Study to Identify Active Components and Potential Targets of Polygonatum sibiricum for Hepatocellular Carcinoma Treatment - Pan, Yuan; Zhang, Xiaoyu; Chen, Chao; Hu, Chunmei (Combinatorial Chemistry & High Throughput Screening, 2025)
<span class=
Keywords: Polygonatum sibiricum